Features of criminal liability for offenses in the field of nature use - Humin, Oleksiy (Global Prosperity, 2023)
The article examines the grounds of criminal liability for crimes against environmental and public safety and health safety of the population of Ukraine. The concepts and types of such grounds, etc., are clarified. The problem of forensic classification of environmental crimes is currently insufficiently researched. In our opinion, it belongs to the number of actual scientific researches. This is explained by the importance of the forensic classification of crimes against the environment for the improvement and development of new methods of investigation of certain types of specified crimes. Human activity, in most cases, has a negative impact on the environment and it is this aspect that causes a criminal aspect in the process of such legal relations. The formation of an ecocentric worldview and bioethical thinking are designed to form eco-positive thinking in society. But society and individual citizens do not always consciously understand the importance of the ecological state of the environment and take actions that directly or indirectly have a negative impact on the environment. Therefore, in order to improve the ecological situation in the state and in general at the global international level, the mechanisms of criminal legal responsibility and prosecution for violations that encroach on fundamental civilizational values contribute to the legal regulation of the investigated issues. A comparative analysis of the criminal law norms of the current legislation of Ukraine regarding environmental crimes with the legislation of the countries of the European Union (hereinafter EU) shows us that there are no similar norms in the Ukrainian criminal legislation. Having analyzed the model criminal law norms of the EU in the field of environmental protection. As a result of the research, a conclusion was formed regarding the need to improve domestic legislation in the field of criminal environmental protection, taking into account modern world trends and the positive experience of foreign legal systems.